Akad as a transactional communication among Generation Z of Banjarese people - Rachmawati, Dewi; Hamdani, Ayu Rakhmi Tiara; Ramonita, Latifa (Jurnal Studi Komunikasi, 2026)
The sale and purchase agreement (akad) has long been a traditional practice in the daily lives of the Banjar community. This study aims to examine the implementation of akad by Generation Z through a transactional communication approach and to analyse how its sustainability contributes to future generations in Banjar society. Using a descriptive qualitative method, this research investigates the construction of meaning surrounding akad in everyday transactional interactions. Data were collected through Focus Group Discussions (FGDs) and in-depth interviews with Generation Z participants. In addition, source triangulation was conducted by involving parents, teachers, community leaders, and sellers. The findings indicate that Generation Z continues to consistently apply akad in their daily transactions. Moreover, informants from all generations emphasised the importance of preserving this practice, as it aligns with the religious and cultural values of the local community.